2003
DOI: 10.1097/00055735-200302000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Management of coincident cataract and uveitis

Abstract: Cataract surgery in a patient with uveitis is more complex than senile cataract extraction, because it involves multiple considerations related to the cause of uveitis, prospects of visual rehabilitation, appropriate surgical timing and technique, and the type and material of the intraocular lens used. Establishing the diagnosis, thorough eye examination, careful patient selection and meticulous control of perioperative inflammation are key elements to a successful visual outcome. Our aims in this article are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 31 publications
1
63
1
Order By: Relevance
“…Cataract surgery in uveitis now carries an excellent visual prognosis [88, 89]. With the exception of lens-induced (phakolytic) uveitis, where cataract surgery is carried out as soon as possible, and Fuchs’ heterochromic uveitis syndrome [90, 91, 92], cataract surgery is usually only contemplated when the eye has been free of active inflammation for a minimum of 3 months, thus the patient may have to suffer many months of poor vision before surgery is undertaken [93, 94]. …”
Section: Epidemiology Of Uveitismentioning
confidence: 99%
“…Cataract surgery in uveitis now carries an excellent visual prognosis [88, 89]. With the exception of lens-induced (phakolytic) uveitis, where cataract surgery is carried out as soon as possible, and Fuchs’ heterochromic uveitis syndrome [90, 91, 92], cataract surgery is usually only contemplated when the eye has been free of active inflammation for a minimum of 3 months, thus the patient may have to suffer many months of poor vision before surgery is undertaken [93, 94]. …”
Section: Epidemiology Of Uveitismentioning
confidence: 99%
“…The most important step in the management of complicated cataract is adequate pre-operative control of the inflammation (Foster et al, 2003). Most authors consider the absence of cells in the anterior chamber synonymous with inflammatory control, as mild cellular reaction in the vitreous persist even in the inactive stage of FHI (Tan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that hydrophobic acrylic lenses have the best capsular biocompatibility and that hydrophilic acrylic lenses exhibit the best uveal biocompatibility [10]. Some studies have suggested that IOLs with PMMA or acrylic optics are more favorable in uveitic patients [11,12]. Decreased incision size and reduced contact between IOL and uveal tissue appear significant for preventing postoperative inflammation [10,13,14].…”
Section: Discussionmentioning
confidence: 99%